2006
DOI: 10.1007/s00421-006-0327-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of recovery mode (passive vs. active) on time spent at maximal oxygen uptake during an intermittent session in young and endurance-trained athletes

Abstract: The aim of this study was to analyze the effects of recovery mode (active/passive) on time spent at high percentage of maximal oxygen uptake (VO2max) i.e. above 90% of VO2max (t90VO2max) and above 95% of VO2max (t95VO2max) during a single short intermittent session. Eight endurance-trained male adolescents (15.9 +/- 1.4 years) performed three field tests until exhaustion: a graded test to determine their VO2max (57.4 +/- 6.1 ml min(-1) kg(-1)), and maximal aerobic velocity (MAV; 17.9 +/- 0.4 km h(-1)), and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
52
1
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 45 publications
10
52
1
7
Order By: Relevance
“…The percentage of participants attaining 95% of peak VO 2 in SI is relatively similar to the findings of Thevenet et al (2007a) and Tardieu-Berger et al (2004) that used an identical SI protocol in endurance-trained adolescents. However, in other studies, a higher percentage of endurance-trained adolescents attained 95% of VO 2 max in a SI protocol at 105% MAV (Thevenet et al 2007b(Thevenet et al , 2008. The t90 and t95 in our study for SI were close to those reported for 30-30-s protocols at 100-110% of MAV (or velocity at VO 2 max) in endurance-trained adolescents (Thevenet et al 2007a) or adults (Millet et al 2003a).…”
Section: Effects Of the Exercise Protocol On Exercise Durationsupporting
confidence: 87%
“…The percentage of participants attaining 95% of peak VO 2 in SI is relatively similar to the findings of Thevenet et al (2007a) and Tardieu-Berger et al (2004) that used an identical SI protocol in endurance-trained adolescents. However, in other studies, a higher percentage of endurance-trained adolescents attained 95% of VO 2 max in a SI protocol at 105% MAV (Thevenet et al 2007b(Thevenet et al , 2008. The t90 and t95 in our study for SI were close to those reported for 30-30-s protocols at 100-110% of MAV (or velocity at VO 2 max) in endurance-trained adolescents (Thevenet et al 2007a) or adults (Millet et al 2003a).…”
Section: Effects Of the Exercise Protocol On Exercise Durationsupporting
confidence: 87%
“…In this situation, the increased O 2 demand of the activity between sprints may create a competition for O 2 between PCr resynthesis and other processes such as lactate oxidation, oxymyoglobin replenishment, and the O 2 demand of the activity (Spencer et al 2006), thereby reducing PCr resynthesis. Supporting this, reduced PPO during repeated sprints with active versus passive recovery has been demonstrated in young participants (mean age 15.9 years; Thevenet et al 2007). This incomplete PCr resynthesis may explain why sprint times progressively slowed throughout the protocol, in line with some previous work Morris et al 2003).…”
Section: Sprint Timesmentioning
confidence: 83%
“…According to Dupont et al (2003), a lower coefficient of variation is obtained when the calculation of t _ VO 2 max is based on _ VO 2 values higher than 95% of _ VO 2 max : Moreover, it still remains whether it is more efficient to maintain _ VO 2 max for a few minutes or to tax 90% of _ VO 2 max for a longer period (Astrand and Rodahl 1986). Therefore, the calculation of the time spent at a high percentage of _ VO 2 max (above 90% ðt90 _ VO 2 max Þ or 95% of _ VO 2 max ðt95 _ VO 2 max Þ) could be interesting to evaluate the interest of an exercise to develop _ VO 2 max : Intermittent exercise (IE) alternating 30s of high and low intensity runs (30s IE) is frequently used in endurance sports to develop performance (Billat 2000b;Tardieu-Berger et al 2004 ;Thevenet et al 2007). It allows a high level of oxygen uptake to be elicited (Astrand et al 1960;Christensen et al 1960;Billat et al 2000b;Demarie et al 2000;Millet et al 2003a, b;Tardieu et al 2004;Midgley et al 2007;Thevenet et al 2007) and longitudinal studies have demonstrated its effectiveness in improving _ VO 2 max (Gorostiaga et al 1991;Overend et al 1992;Burke et al 1994).…”
mentioning
confidence: 99%